Efficacy and safety of Usights UC100 illuminated microcatheter in microcatheter-assisted trabeculotomy - Shuo Yu; Ke Xu; Chun Zhang (International Journal of Ophthalmology, 2024)
AIM: To evaluate the efficacy and safety of Usights UC100 illuminated microcatheter in microcatheter-assisted trabeculotomy (MAT). METHODS: Totally 10 eyes of 10 patients with primary open angle glaucoma (POAG) who underwent MAT facilitated by Usights UC100 (5 eyes) or iTrack (5 eyes) were reviewed. The success of this surgery was defined as intraocular pressure (IOP) <22 mm Hg with >30% reduction, without oral glaucoma medications, or additional glaucoma surgery. RESULTS: The mean pre-operative IOP was 25.38±10.22 mm Hg in the Usights UC100 group and 19.98±3.87 mm Hg in the iTrack group. MAT was achieved in all eyes in both groups. The success rates for the Usights UC100 group and iTrack groups were in all and 4 eyes, respectively. Both microcatheters produced a statistically significant reduction in IOP, and eyes using Usights UC100 achieved a lower IOP than the iTrack group at 3mo follow-up (12.58±1.52 and 14.84±1.89 mm Hg, respectively), but no statistical significance was there. No severe side effects were observed in either group. CONCLUSION: MAT using Usights UC100 or iTrack both achieve significant pressure reduction in cases of POAG, and Usights UC100 is as safe as iTrack.